KAJIAN OPERASIONAL TEMPAT PELELANGAN IKAN (TPI) DAN KESEJAHTERAAN MASYARAKAT NELAYAN (Studi Kasus Desa Watukarung Kecamatan Pringkuku Kabupaten Pacitan) - Syafruddin, Eki; Maskie, Ghozali; Pratama, Yogi Pasca (EP FEB UNS, 2014)
This study is motivated by great marine potential, but the condition of the fishing community is generally poor. This is a potential obstacle for fishing communities to encourage the dynamics of development in their region. Sub-district Pringkuku in 2008 has a total of 529 fishermen with 62.94 percent in the poor category. The purpose of this study is (1) to know the operational of Fish Auction Site (TPI) of Watukarung Village and (2) to know how the operation of Fish Auction Site (TPI) in improving the prosperity of local fishermen community. This study uses descriptive and qualitative methods. Methods of data collection by interviewing and documenting information from 11 informants who have roles in different economic interactions. The results of this study are (1) the operational of the fishermen depends on the interaction of the fishermen and the fisherman who are tied up with a unique profit-sharing system that is understood and obeyed by all parties, (2) The fish auction place (TPI) All stakeholders in TPI also influence the formation of the price of catch with auction system. Keywords: coastal, fish auction place, auction, welfareJEL Classifications: D44, 017, Q22